PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP KINERJA PEGAWAI POS PEMBINAAN TERPADU (POSBINDU) KABUPATEN TABALONG - Heldina Sofia (JURNAL KINDAI, 2020)
This study aims to study both partially and simultaneously greater Competence and Motivation on the Performance of Tabalong Integrated Development Post Employees (POSBINDU) and the dominant variables on the Performance of Integrated Development Post (POSBINDU) Tabalong Regency, The method used in this study is the method quantitative and with a total of 80 (eighty), taken with a census of 80 (eighty) people, validity and reliability test research instruments, data were collected using multiple linear regression.The results of this study indicate that (1) Competence and Motivation show partial significance on the Performance of Inpatient Employees at Integrated Development Post (POSBINDU) (2) Competency and Motivation are related significantly simultaneously to the Performance of Inpatient Employees in Integrated Development Post (POSBINDU) and (3) Motivation is a variable that has a dominant influence on the Performance of Inpatient Employees at Integrated Development Post (POSBINDU). R Square of 0.561 which means that the total variation of the independent variables on the accepted variable is 56.1% while the remaining 43.9% is requested by other causes outside of this study.Keywords: Competence, Motivation and Employee Performance.